Kenya Cluster— AICCRA Household Survey Report 2024 - Chesoli, Rose (International Livestock Research Institute, 2024)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) program is dedicated to fostering a climate-smart future for Africa by leveraging science and agricultural innovation. The program seeks to make climate information services (CIS) and climate-smart agriculture (CSA) technologies accessible to more than seven million smallholder farmers across Senegal, Ghana, Mali, Ethiopia, Kenya, and Zambia. By improving access to and adoption of these innovations, AICCRA empowers farmers to anticipate and mitigate climate-related hazards, thereby safeguarding livelihoods and promoting environmental sustainability. In Kenya, AICCRA is led by the International Livestock Research Institute (ILRI) in collaboration with ABC, ICRISAT, and IRI. The program focuses on enhancing farmers' access to and utilization of CIS and CSA technologies. From November 4 to December 7, 2024, a survey was conducted in eastern Kenya to assess farmers' access to and use of CIS and CSA, evaluating their impact on knowledge, attitudes, skills, and practices (KASP). The survey also examined the benefits of CIS and CSA adoption, resilience to climate hazards, dissemination effectiveness, and short-term outcomes such as income, productivity, food security, and resilience.